Mechanism of Endoplasmic Reticulum Stress in Cerebral Ischemia - Han, Yu; Yuan, Mei; Guo, Yi-Sha; Shen, Xin-Ya; Gao, Zhen-Kun; Bi, Xia (Frontiers in Cellular Neuroscience, 2021)
Endoplasmic reticulum (ER) is the main organelle for protein synthesis, trafficking and maintaining intracellular Ca2+ homeostasis. The proportion of ischemic stroke in central nervous system diseases is increasing with each passing year, which is a prevalent reason of death and disability in the world. Cerebral ischemia causes several stress responses where ER in stress state initiates unfolded protein response (UPR) due to accumulation of misfolded and unfolded protein as well as Ca2 + overload, which is associated with a specialized set of inflammatory and apoptotic signaling pathways controlling the fate of nerve cells. Mild ER stress promotes cells to break away from danger signals and enter the adaptive procedure with the activation of pro-survival mechanism to rescue ischemic injury, while chronic ER stress generally serves as a detrimental role on nerve cells via triggering diverse pro-apoptotic mechanism. A reasonable understanding and exploration of the underlying molecular mechanism related to ER stress and cerebral ischema is a prerequisite for a major breakthrough in stroke treatment in the future. This review focuses on recent findings of the ER stress as well as the progress research of mechanism in ischemic stroke prognosis provide a new treatment idea for recovery of cerebral ischemia.